2011
DOI: 10.1007/s00220-011-1294-x
|View full text |Cite
|
Sign up to set email alerts
|

The Quantum Double Model with Boundary: Condensations and Symmetries

Abstract: Associated to every finite group, Kitaev has defined the quantum double model for every orientable surface without boundary. In this paper, we define boundaries for this model and characterize condensations; that is, we find all quasi-particle excitations (anyons) which disappear when they move to the boundary. We then consider two phases of the quantum double model corresponding to two groups with a domain wall between them, and study the tunneling of anyons from one phase to the other. Using this framework w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
277
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(290 citation statements)
references
References 16 publications
11
277
1
1
Order By: Relevance
“…This might result in the simple permuting-type defect lines introducing entropic protection to Abelian systems. Our analysis only applies to Abelian quantum doubles, i.e., qudit stabilizer codes, therefore, entropic protection of quantum doubles based on non-Abelian groups (or of models that are not quantum doubles of any group) is not ruled out, especially since one can think of a variety of defect lines which can arise in such models [27]. One can also consider constructions where lower-dimensional topological systems are coupled to an ancillary system, and this coupling modifies the dynamics of the original model [5,28].…”
Section: Discussionmentioning
confidence: 99%
“…This might result in the simple permuting-type defect lines introducing entropic protection to Abelian systems. Our analysis only applies to Abelian quantum doubles, i.e., qudit stabilizer codes, therefore, entropic protection of quantum doubles based on non-Abelian groups (or of models that are not quantum doubles of any group) is not ruled out, especially since one can think of a variety of defect lines which can arise in such models [27]. One can also consider constructions where lower-dimensional topological systems are coupled to an ancillary system, and this coupling modifies the dynamics of the original model [5,28].…”
Section: Discussionmentioning
confidence: 99%
“…We will be most interested in studying these defects in explicit lattice models [6][7][8][9][10], and in particular the model introduced by Bombin [6]. Essentially the same defects have also been studied in Chern-Simons theories [11][12][13].…”
mentioning
confidence: 99%
“…Third, in the case with finite groups, the Levin-Wen model is dual to the Kitaev quantum double model. Shor et al have shown that the boundary degrees of freedom in the Kitaev model defined by a finite group G live in a subgroup of G [37], which in the dual Levin-Wen model corresponds to a Frobenius algebra in the UFC of the representations of G.…”
Section: A Gapped Energy Spectrum For Each Boundary Hamiltonian Togetmentioning
confidence: 99%
“…It is worth noting that there has been a few studies of the boundary Hamiltonians in the Kitaev model [36][37][38][39], as well as a study of the Levin-Wen model [17] with boundary in the language of module categories. While our approach is systematic and easier to access by the condensed matter community, we shall discuss in section 10 the relation between our approach and the one taken by Kitaev and Kong [17].…”
Section: Jhep01(2018)134mentioning
confidence: 99%